ASSESSMENT OF THE PSYCHOLOGICAL STATUS OF PATIENTS WITH GYNECOLOGICAL CANCER IN THE PROCESS OF PSYCHOLOGICAL REHABILITATION - E. V. Pestereva (Učenye Zapiski Sankt-Peterburgskogo Gosudarstvennogo Medicinskogo Universiteta im. Akad. I.P. Pavlova, 2018)
Introduction. Psychological care as the essence of psychological rehabilitation in оoncology is based on the working with the experiences of patients caused by cancer. The specificity of the patient’s experience is determined by the localization of the tumor and the importance attached to the patient’s diseased part of the body. Gynecological cancer affects important areas for women related to femininity, motherhood, affecting her sexual life and family relations. The objective is the psychological study of the experiences of oncogynecological patients, the specificity of which must be taken into account in the process of psychological rehabilitation. Material and methods. 41 patients aged from19 to 45 years with oncogynecological diseases at different stages of treatment were examined. The data of the clinical and psychological interviews were supplemented by the results of psychodiagnostic tests -TOBOL, Hissen questionnaire of somatic complaints, EQRTCQLQ-C30. Results. Long period of denial of the malignant disease is not characteristic for oncogynecological patients. Disturbing component in patients at the stage of «before operation» and dysphoric component in patients at the stage of «after surgery» were dominated on the background of ergopathic reactions to the disease in the structure of attitude to the disease. The high intensity of complaints of female patients about their health, including non-specific, indicating the psychosomatic component of the patient’s suffering was revealed. The life quality of patients is interconnected with their idea of the types of treatment, their dangers. It is shown that cancer is a psychological crisis not only for the oncogynecological patient, but also for other members of her family, especially her husband. Conclusions. Psychological care for oncogynecological patients in the process of psychological rehabilitation should be based on the account of their deep experiences, which are determined by the self-relationship of women and the adoption of themselves and that patients are not aware, but affect their attitude to the disease and treatment and, thereby, determine their life quality. Psychological care aimed to building new relationships, which are adequate to the situation of the disease, is necessary for the whole family of the patient.